Economic Analysis on Processing Organic Pineapple Peel Waste as Eco-Enzyme Liquid Fertilizer - Bilqis Aprilia Salima (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The objective of this research is to analyze, evaluate, and compare the feasibility analysis results of liquid fertilizer production from pineapple peel waste based on an economic perspective. Mass balance and several economic parameters such as Gross Profit Margin (GPM), Cumulative Net Present Value (CNPV), Internal Rate of Return (IRR), Payback Period (PBP), Break-Even Point (BEP), and Profitability Index (PI) are calculated to assess the project's feasibility from an economic standpoint. The results indicate that the project has the potential for profitability in large-scale production, as it requires a short time to recover the investment costs, approximately 3 years based on the PBP analysis. Furthermore, in terms of external tax factors, despite a tax rate of 100%, the project still generates profits. However, the profits generated are not as much as a 10% tax rate. Nevertheless, the project remains profitable.